IJABE Editorial: Open access leads to success - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
International Journal of Agricultural and Biological Engineering (IJABE, www.ijabe.org) is a peer reviewed open access international journal, launched in 2008. Open access (OA) means unrestricted online access to peer-reviewed scholarly research. OA literature is free, digital, and available to anyone online. An open-access article has limited copyright and licensing restrictions which means anyone, anywhere, with access to the Internet may read, download, copy, and distribute that article. As an OA journal, the papers published in IJABE are freely accessible online immediately upon publication via the IJABE website. With the OA strategy, IJABE can reach a broader spectrum of readership by removing price barriers (subscriptions, licensing fees, pay-per-view fees) that some individual readers may experience.